Implementing the Problem Posing Learning Model to Enhance Student Engagement and Higher-Order Thinking Skills (HOTS) in Islamic Education: A Case Study at Ma’had Al-Buus Al-Islamiah, Southern Thailand - Aida Hayani; Moh. Farhan; Akhmad Zulfikar Khabibulloh; Ahsanul Fuadi; Muhammadnur Kora (AL-ISHLAH: Jurnal Pendidikan, 2025)
Student engagement and Higher-Order Thinking Skills (HOTS) are critical in Islamic education, particularly within traditional settings such as Ma’had Al-Buus Al-Islamiah, Southern Thailand. This study investigates the impact of the problem-posing learning model in enhancing these two dimensions. This quasi-experimental study employed a pretest-posttest control group design involving 80 tenth-grade students. Participants were divided into an experimental group (n = 40), which received instruction using the problem-posing model, and a control group (n = 40), which followed conventional teaching methods. Data were collected through classroom observations, validated HOTS tests, and engagement questionnaires. The findings reveal that the problem-posing model significantly improved both student engagement and HOTS. Engagement levels reached 91.6% in the experimental group compared to 67.8% in the control group. HOTS, measured through N-Gain scores, increased to 91.93% in the experimental group versus 84.90% in the control group. Statistical analyses confirmed the significance of these differences (p 0.05), with large effect sizes. The results suggest that the problem-posing model promotes active learning, critical thinking, and problem-solving, even within culturally traditional Islamic education environments. It aligns with constructivist and dialogical learning theories by fostering student-centered inquiry and deeper cognitive engagement. Implementing the problem-posing learning model in Islamic education settings can effectively enhance both engagement and higher-order thinking. These findings support the adoption of innovative pedagogies to improve student outcomes in religious and general educational contexts.